2019
DOI: 10.3390/en12112113
|View full text |Cite
|
Sign up to set email alerts
|

New Perspective on Performances and Limits of Solar Fresh Air Cooling in Different Climatic Conditions

Abstract: The study carried out by simulation, concerns the thermal behavior of an office building’s solar fresh air cooling system, based on a LiBr-H2O absorption chiller in different climatic conditions. The coefficient of performance (COP) and the solar fraction were considered performance parameters and were analyzed with respect to the operating limits—the risk of crystallization and maintaining at least a minimum degassing zone. A new correlation between the required solar hot temperature and the cooling water tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The absorption process can involve a phase change or chemical reaction, where the sorbate diffuses into the liquid or solid sorbent [19]. Common absorption materials include aqueous solutions of calcium chloride (CaCl2), lithium chloride (LiCl), lithium bromide (LiBr), sodium hydroxide (NaOH), potassium hydroxide (KOH), and ammonia [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The absorption process can involve a phase change or chemical reaction, where the sorbate diffuses into the liquid or solid sorbent [19]. Common absorption materials include aqueous solutions of calcium chloride (CaCl2), lithium chloride (LiCl), lithium bromide (LiBr), sodium hydroxide (NaOH), potassium hydroxide (KOH), and ammonia [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this period, several configurations have been studied and analyzed in terms of stages, absorberrefrigerant pairs, drive medium, applications and cooling capacities. In the literature, studies of solar cooling thermal systems have been found with single-effect absorption machines and driven by various types of solar collectors: with nonconcentrating or stationary solar collectors [4,5,6,7,8,9,10,11,12,13,14,15,16], with parabolic cylinder collectors [6,14,17,18] and with linear Fresnel collectors [19]. Also, systems with absorption machines with two or more stages and with various types of solar collectors: with parabolic cylinder collectors [4,20] and with linear Fresnel collectors [21].…”
Section: Introductionmentioning
confidence: 99%
“…Reductions of 19.35% in annual cooling energy use, and 7.2% reduction in total annual energy use were achieved. Abrudan et al [30] studied the implementation of absorption cooling equipment under different climatic conditions. They proposed new correlations between the solar hot water temperature and the cooling water temperature in order to avoid both crystallization and the reduction of the degassing zone below 6%.…”
mentioning
confidence: 99%